2012
DOI: 10.1007/s10103-012-1056-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Er,Cr:YSGG laser irradiation on enamel caries prevention

Abstract: The objective of this study was to evaluate the effects of chromium:yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser irradiation on the acid resistance of dental enamel. Forty human enamel samples were divided into four groups. They were manually irradiated with an Er,Cr:YSGG laser device (λ = 2.78 µm, 20 Hz, 20 s), in a scanning mode, with and without water cooling, according to the following parameters: Group 1: 0.25 W, 62.5 J/cm(2), no water cooling; group 2: 0.25 W, 62.5 J/cm(2), 5.0 ml/min; group 3: 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
4
19
1
Order By: Relevance
“…This finding corroborates the results of some previous authors (22-24) who observed no significant increase in caries resistance of the specimens irradiated with the Er:YAG or Er,Cr:YSGG lasers compared to the control group. The outcomes of this study, however, are in contrast to the studies that indicated caries inhibitive effects of erbium lasers (11-13). de Freitas et al (12) reported that the specimens submitted to the Er,Cr:YSGG laser at 8.5 J/cm2 showed 64% caries inhibition which was comparable to the cariostatic effect of the samples treated with a NaF dentifrice.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…This finding corroborates the results of some previous authors (22-24) who observed no significant increase in caries resistance of the specimens irradiated with the Er:YAG or Er,Cr:YSGG lasers compared to the control group. The outcomes of this study, however, are in contrast to the studies that indicated caries inhibitive effects of erbium lasers (11-13). de Freitas et al (12) reported that the specimens submitted to the Er,Cr:YSGG laser at 8.5 J/cm2 showed 64% caries inhibition which was comparable to the cariostatic effect of the samples treated with a NaF dentifrice.…”
Section: Discussioncontrasting
confidence: 89%
“…Hossain et al (26), however, indicated that Er:YAG laser without water mist was more effective in caries prevention than when it was used with water coolant. This has also been emphasized by other authors (13) who found that water, even in minimal amounts, was not favorable for the preventive effect of laser irradiation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For the acid challenge, samples were submitted to a pHcycling procedure, modified from previously described protocols 13 , 14 . The demineralization solution (pH=4.3) consisted of 2 mmol/L of Ca and 2 mmol/L of phosphate in buffer solution of acetate 0.075 mol/L, and the remineralization solution (pH=7.0) consisted of 1.5 mmol/L of Ca, 0.9 mmol/L of phosphate and 150 mmol/L of potassium chloride.…”
Section: Methodsmentioning
confidence: 99%
“…However, for caries prevention, it is important that the laser does not ablate the treated surface, but change the tissue morphologically or chemically. Therefore, to achieve the preventive effect, studies have been performed with low energy densities (sub-ablative parameters) and without water cooling 1 , 2 , 9 , 10 , 14 . It was demonstrated that the irradiation of the enamel surface with an Er,Cr:YSGG laser device, using an energy density of 8 J/cm 2 , promotes a sufficient temperature increase to change the chemical structure of enamel, turning it into a less soluble structure 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%